2023
DOI: 10.1101/2023.01.19.524809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secretory and transcriptomic responses of mantle cells to low pH in the Pacific oyster (Crassostrea gigas)

Abstract: Since the Industrial Revolution, the concentration of atmospheric carbon dioxide (CO2) due to anthropogenic activities has increased at unprecedented rates. One-third of the atmospheric anthropogenic CO2 emissions are dissolved in the oceans affecting the chemical equilibrium of seawater, which in turn leads to a decrease in pH and carbonate ion (CO32-) concentration, a phenomenon known as ocean acidification (OA). This chemical disequilibrium can be detrimental to marine organisms (e.g., mollusks) that fabric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…These results indicated that chalky layer formation was dominated by different mantle regions (ME or MC) under distinct physiological conditions of oyster (normal or shell repair condition), respectively. A recent study on ocean acidification proposed that chalky layer was produced by the mantle pallial of oysters [ 57 ]. This observation might only represent the regulation of chalky deposition by mantle pallial under low pH conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that chalky layer formation was dominated by different mantle regions (ME or MC) under distinct physiological conditions of oyster (normal or shell repair condition), respectively. A recent study on ocean acidification proposed that chalky layer was produced by the mantle pallial of oysters [ 57 ]. This observation might only represent the regulation of chalky deposition by mantle pallial under low pH conditions.…”
Section: Resultsmentioning
confidence: 99%
“…C3 compliment is a recognized component of cnidarian innate immune system (Miller et al, 2007;Schwarz et al, 2008;Kvennefors et al, 2010;Palmer and Traylor-Knowles, 2012;Ocampo et al, 2015). Tenascin-R (TNR) is also known as ryncolin-4 is considered part of the innate immune system, involved with activating the Compliment pathway, and is upregulated in acidic conditions (OmPraba et al, 2010;Zúñiga-Soto et al, 2023). To be activated, proton-dependent MCTs need to bind immuno-globulin transmembrane glycoproteins (Muramatsu, 2016).…”
Section: Links To Immune Responsesmentioning
confidence: 99%